Affective polarization and its relationship to immersion in digital content - Ali Fakher Abed, Dr. (lark, 2024)
This research deals with the issue of affective polarization with which politicians influence the public, and how this polarization occurs, the researcher dealt with the concept of political polarization by explaining and theoretically rooting it because it is a term that is rarely used in Arab studies, and even the studies that dealt with it did not deal with it in-depth, nor did they establish a theoretical foundation for it. As well as the concept of immersion in digital content, which we can now measure because it occurs on the network.The research problem included the following basic question: What is the relationship between the process of immersion in digital content and the process of political polarization? From this question other questions branched out, and the research was descriptive research, in which the survey method was employed to reach the desired results. The research community included the population of the city of Baghdad from politically polarized people, and from those who agreed to answer the research questions and interact with its requirements, and the sample number was Search (180) individuals. The most prominent results showed that the digital behavior of a person immersed in content is that he is trying to learn more about the topic he is interested inIt remains for a long time with specific contents, and one of the results and repercussions of political polarization after immersing individuals in the digital content of party pages is that they view party leaders in a negative light.
Keywords: affective polarization, political polarization, immersion in digital content, politics and new media, social media platforms